Thermal recovery of organic solid waste by aerobic process: fuel derived from food waste - PEREIRA DE SÁ, FERNANDO; CARDOSO DE LIMA BORGES, ELISANGELA (Latin American Journal of Energy Research, 2025)
The inadequate disposal of food waste represents an environmental and energy challenge. Pressurized aerobic digestion emerges as an innovative alternative, enabling the reduction of residual mass and the production of biocompost with energy characteristics. In this study, food waste was subjected to controlled aerobic digestion for 14 days, resulting in mass reductions ranging from 60% to 79%. The obtained biocompost was characterized in terms of its physicochemical composition, with carbon content ranging from 37% to 44% and low sulfur content (<0.2%). Thermal analyses (TG/DSC) indicated multiple combustion stages, with a profile favorable for sustained heat generation. The higher heating value (HHV) ranged from 15.46 to 17.47 MJ/kg, values comparable to charcoal and higher than many agricultural-origin biofuels. The results demonstrate the viability of the process as a fast strategy for energy valorization of food waste, with potential to reduce environmental impacts and contribute to the renewable energy matrix.